Experiment Research and Simulation Analysis of Regenerative Oxygen-enriched Combustion Technology. (2015) - Guo, Kehong; Shi, Weihua; Wu, Daohong
Abstract: As a kind of high temperature combustion technology, oxygen-enriched combustion is widely used in the fields of glass industry, metallurgical industry and thermal power engineering. In order to further increase the combustion temperature and save energy simultaneously, this paper researched and analyzed the combustion mode which combines the regenerative combustion technology and oxygen-enriched combustion, and contrastively analyzed each combustion features of regenerative oxygen-enriched combustion technology. CFD engineering simulation software FLUENT is adapted to simulating combustion under the operating condition. Through comparison of simulation and experimental result, the influence of oxygen concentration on combustion in furnace and temperature is confirmed; meanwhile under this condition, energy consumption is reduced. The research result indicated that this technology not only increases temperature and decrease operating cost, it also has more widely application scope.